2021
DOI: 10.14504/ajr.8.4.2
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Characterization of Cellulose Nanofibers from Flaxseed Fiber Bundles

Abstract: In recent decades, rational management of agricultural residues presented a new approach for extraction, characterization, and utilization of cellulose nanofibers (CNF). In this context, the valorization of flaxseed fibers, providing an annual yield of millions of metric tons, as an abundant sustainable fiber source, was carried out. The cleaned and ground raw material was delignified and bleached, followed by 2,2,6,6-tetramethylpiperidine-1-oxyl radical (TEMPO)/NaBr/NaClO oxidization along with mechanical ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 45 publications
0
1
0
Order By: Relevance
“…The XRD results showed that the approximate positions of the diffraction peaks were 2θ = 15.3 • , 16.4 • , 22.5 • and 34.2 • [Fig. 3(b)], indicating the characteristic diffraction structure of cellulose I (native cellulose) (Azhar et al, 2021). The characteristic peaks of the sample appeared near 16.4 • , 22.5 • and 35 • , indicating that the sample contained crystallized and amorphous structures.…”
Section: Xrd Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…The XRD results showed that the approximate positions of the diffraction peaks were 2θ = 15.3 • , 16.4 • , 22.5 • and 34.2 • [Fig. 3(b)], indicating the characteristic diffraction structure of cellulose I (native cellulose) (Azhar et al, 2021). The characteristic peaks of the sample appeared near 16.4 • , 22.5 • and 35 • , indicating that the sample contained crystallized and amorphous structures.…”
Section: Xrd Analysismentioning
confidence: 99%
“…XRD analysis was conducted following the method of Azhar et al (2021). The crystallinities of samples were determined using an X-ray diffractometer (Rigaku D/max2500, Rigaku Co., Ltd, Tokyo, Japan) with filtered Cu Kα radiation (λ = 0.1540 nm) at 40 kV and 40 mA.…”
Section: X-ray Diffraction Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Sloneker 1971 [44] Flaxseed fiber Assessment and characterization of flaxseed fiber bundles CNF's Azhar et al 2021 [45] Nopal Cactus Cellulose from cactus plant: Extraction and Isolation Ouhammou et al 2022 [46] Mulberry Mulberry cellulose whiskers: A unique biomass production method…”
Section: Sugarcane Bagassementioning
confidence: 99%
“…[1][2][3] Researchers are constantly exploring various applications based on cellulose due to its biodegradability. 4,5 Its ability to serve as a sustainable renewable natural resource is vital in this era of eco-friendliness and sustainability. 6 Cellulose has a densely packed glucan chain structure which improves its mechanical strength to support cellular networks and introduce various surface modifications.…”
Section: Introductionmentioning
confidence: 99%